2022
DOI: 10.3390/molecules27155044
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Induced and Recyclable g-C3N4 Catalyzed C-H Sulfenylation of Quinoxalin-2(1H)-Ones

Abstract: A sunlight-promoted sulfenylation of quinoxalin-2(1H)-ones using recyclable graphitic carbon nitride (g-C3N4) as a heterogeneous photocatalyst was developed. Using the method, various 3-sulfenylated quinoxalin-2(1H)-ones were obtained in good to excellent yields under an ambient air atmosphere. Moreover, the heterogeneous catalyst can be recycled at least six times without significant loss of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…At the same time, an electron from the CB is transferred to O2 (air) to form O2 •− , which has been confirmed by EPR analysis using 5,5-dimethyl-1-pyrroline (DMPO) as a spin trapping agent. Next, O2 In the same year, Xie et al reported a sunlight-induced and g-C3N4-catalysed sulfenylation reaction of quinoxalin-2(1H)-ones under air conditions (Scheme 7) [44]. The reactions of this method offer a very attractive and practical way to selectively obtain a wide variety of 3-sulphated quinolin-2(1H)-ones in good to excellent yields.…”
Section: Scheme 3 G-c3n4-catalyzed Divergent Heterogeneous Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, an electron from the CB is transferred to O2 (air) to form O2 •− , which has been confirmed by EPR analysis using 5,5-dimethyl-1-pyrroline (DMPO) as a spin trapping agent. Next, O2 In the same year, Xie et al reported a sunlight-induced and g-C3N4-catalysed sulfenylation reaction of quinoxalin-2(1H)-ones under air conditions (Scheme 7) [44]. The reactions of this method offer a very attractive and practical way to selectively obtain a wide variety of 3-sulphated quinolin-2(1H)-ones in good to excellent yields.…”
Section: Scheme 3 G-c3n4-catalyzed Divergent Heterogeneous Reactionmentioning
confidence: 99%
“…In the same year, Xie et al reported a sunlight-induced and g-C 3 N 4 -catalysed sulfenylation reaction of quinoxalin-2(1 H )-ones under air conditions ( Scheme 7 ) [ 44 ]. The reactions of this method offer a very attractive and practical way to selectively obtain a wide variety of 3-sulphated quinolin-2(1 H )-ones in good to excellent yields.…”
Section: Direct C–h Functionalization Of Quinoxalin-2(1 H ...mentioning
confidence: 99%
“…[16,17] Chemical advances in total synthesis, synthetic methods, chemical biology, and drug discovery have all focused on pyrazines, which have a six-membered aromatic structure with two nitrogen atoms arranged in a 1,4-orientation embedded within a carbon framework and exhibit unique chemical reactivity profiles. [18,19] Many biological studies of pyrazine and hybrid compounds have shown their therapeutic efficacy concerning human health and sickness after looking at the ideal cavity and structural core of pyrazine nitrogen. [20,21] Some important pyrazines (amiloride, bortezomib, pyrazinamide) and many more are shown in Figure 2 as being on the 2019 WHO's Model List of Essential Medicines.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, the carbamoyl-radical-triggered cascade cyclization reaction of N3-alkenyl-tethered quinazolinones to afford amide-containing quinazolinones has never been reported. With our continuing interest in radical chemistry [ 64 , 65 , 66 , 67 , 68 ], herein, we report a metal-free protocol for the synthesis of amide-substituted polycyclic quinazolinones through the cascade radical carbamoylation/cyclization reaction of N3-alkenyl-tethered quinazolinones with oxamic acids as a readily available carbamoyl radical source ( Scheme 1 b).…”
Section: Introductionmentioning
confidence: 99%